'A strange kind of balance': Inpatient hospice volunteers' views on role preparation and training. (2nd November 2017) - Dean, Antonia; Willis, Susan
Abstract : There is a paucity of research on the training needs of hospice volunteers. In the UK, there have been calls for the development of a core curriculum for hospice volunteers but debate exists around the potential for unnecessary 'professionalization' of volunteers, diluting their unique contribution. This qualitative, focus group study explores the views of UK inpatient hospice volunteers regarding initial training for role preparation. Following thematic analysis, six themes emerged: (a) role preparation, (b) common sense and life experience, (c) role challenges, (d) benefits and boundaries of training, (e) training content, (f) training delivery. Volunteers perceived initial training to be important in increasing confidence and set out several areas where they felt additional training would be valuable. There was some disagreement about how training contributed to professionalization and the extent of education with respect to role boundaries. This study will inform local practice, shaping the education and support of future volunteers, and adds to the wider evidence-base surrounding the development of this crucial group within the hospice workforce.